UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAN FRAKSI DARI AKAR DAN BATANG TUMBUHAN SEKUNYIT (Fibraurea tinctoria Lour) - Rahayu Utami; Dwi Winarsih; Armon Fernando; Haiyul Fadhli; Mustika Furi; Emma Susanti (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Sekunyit (Fibraurea tinctoria Lour) is plant species that has been using widely as traditional medicine such as a cure for diarrhea. This study was conducted to determine the antibacterial activity of extract and fractions of its root and stem against bacteria that cause diarrhea. The sample of root and stem were macerated with ethanol and then followed by ultrasonication process for 30 minutes. Fractionation process was performed by acid-base method using three different solvents which were n-hexane, chloroform and n-butanol. The extract and fractions were tested for its antibacterial activity using agar diffusion method at tested concentrations of 30; 15; 7.5; 3.75 and 1.88%. The result showed that the ethanol extract, n-hexane, chloroform A and chloroform B fractions of the root and stem provided antibacterial activity against all tested bacteria with weak to medium activity. Whereas the n-butanol fraction did not give any activity, either to Escherichia coli, Salmonella typhi, Staphylococcus aureus as well as Vibrio cholerae.